2018
DOI: 10.1097/aln.0000000000002186
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Neural Network Model for Prediction of Postoperative In-hospital Mortality

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background The authors tested the hypothesis that deep neural networks trained on intraoperative features can predict postoperative in-hospital mortality. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
147
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(157 citation statements)
references
References 30 publications
(29 reference statements)
5
147
4
1
Order By: Relevance
“…In line with prior studies, variables with >10% missing values were excluded from consideration, 17,20 and data were split randomly as 80% training and 20% testing (stratified on patient mortality at last known follow-up, to maintain approximately even mortality rates between training and testing sets). 21 Using the training data, categorical measures were divided into binary variables to retain clinically relevant distinctions between categories, while eliminating potentially inaccurate ordinal relationships between categories. For highly collinear variable pairs, the variable having the largest mean absolute correlation with other variables in the training set was excluded from the set.…”
Section: Me Thodsmentioning
confidence: 99%
“…In line with prior studies, variables with >10% missing values were excluded from consideration, 17,20 and data were split randomly as 80% training and 20% testing (stratified on patient mortality at last known follow-up, to maintain approximately even mortality rates between training and testing sets). 21 Using the training data, categorical measures were divided into binary variables to retain clinically relevant distinctions between categories, while eliminating potentially inaccurate ordinal relationships between categories. For highly collinear variable pairs, the variable having the largest mean absolute correlation with other variables in the training set was excluded from the set.…”
Section: Me Thodsmentioning
confidence: 99%
“…To determine which features were most important to the classification models, we 144 examined the model weights for linear models, the feature (Gini) importance for the 145 random forest models, and the feature weight (number of times a feature appears in a 146 tree) for the gradient boosted tree models. Previous work [11] has shown that integrating a measure of preoperative risk into a 149 postoperative mortality risk prediction model increases the model performance. We Lee et al [11], we replaced the ASA status feature with the preoperative risk score 154 (generated using the random forest model with preoperative features and imputed-ASA 155 scores) and trained the model on the same cohort used for preoperative risk prediction.…”
mentioning
confidence: 99%
“…Previous work [11] has shown that integrating a measure of preoperative risk into a 149 postoperative mortality risk prediction model increases the model performance. We Lee et al [11], we replaced the ASA status feature with the preoperative risk score 154 (generated using the random forest model with preoperative features and imputed-ASA 155 scores) and trained the model on the same cohort used for preoperative risk prediction. 156 The intraoperative data were preprocessed in the same manner as described in [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations